2018
DOI: 10.5539/ies.v11n11p34
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Students’ Misconceptions about the Concepts of Astronomy

Abstract: The purpose of the current study is to conduct developmental comparison of the middle school students' misconceptions about the concepts of astronomy. The sampling of the study is comprised of middle school students attending a private school located in the west of Turkey. A total of 144 students participated in the study. In order to determine the students' perceptions of the concepts of astronomy, a data collection tool consisting of five open-ended questions was developed by the researchers. The data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Since the contents related to astronomy are abstract (Dendup et al, 2021;Kersting et al, 2020), employing effective strategies for teaching and learning astronomy is essential. Moreover, students have misconceptions about astronomy contents (Aksan et al, 2017;Baybars & Can, 2018;Koca, 2019). Therefore, digital technology effectively contributes to teaching and learning abstract concepts like astronomy (Oktay, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the contents related to astronomy are abstract (Dendup et al, 2021;Kersting et al, 2020), employing effective strategies for teaching and learning astronomy is essential. Moreover, students have misconceptions about astronomy contents (Aksan et al, 2017;Baybars & Can, 2018;Koca, 2019). Therefore, digital technology effectively contributes to teaching and learning abstract concepts like astronomy (Oktay, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…Astronomy is one of the earliest disciplines and attracted considerable interest from the people (Baybars & Can, 2018). They also claimed that before the development of writing, people conducted their lives according to the sun and moon they viewed during the day and night.…”
Section: Concepts Of Astronomymentioning
confidence: 99%
“…In recent years, study on the basic concepts of space science and astronomy have been intensively carried out by many researchers around the world (Baybars, 2018;Brunsell & Marcks, 2005;Taşcan, 2013). Brunsell and Marcks (2005) conducted a study on 142 science teachers and employed an astronomy concepts recognition test as a data collection tool.…”
Section: Conception and Misconception In Space Science Among Preservice Teachersmentioning
confidence: 99%
“…The findings also showed that all the variables do not emerge in teachers' knowledge. In another study conducted by Baybars (2018), the conclusion made was that the middle school students also encounter some misconceptions about the basic concepts of astronomy such as the universe, solar system, star, planet and constellation.…”
Section: Conception and Misconception In Space Science Among Preservice Teachersmentioning
confidence: 99%
“…It has also been highlighted that both in-service and pre-service teachers have inadequate alternative conceptions in astronomy [59]. This can influence the way they approach teaching, and it directly affects students' understanding of science [60].…”
mentioning
confidence: 99%